The Role of Entrepreneurship in Encouraging Sustainable Economic Development - Prasta, Julius Gofinda; Djastuti, Indi (LifeSciFi, 2024)
Entrepreneurship has an important role in encouraging sustainable economic development, especially in developing countries. This article aims to analyze how entrepreneurship can contribute to economic growth that not only focuses on financial gains, but also pays attention to social and environmental aspects. In this context, entrepreneurship serves as a driving force for innovation, job creation, and development of local communities. Through a qualitative approach and literature analysis, this study explores several aspects that show a positive relationship between entrepreneurship and sustainable economic development. First, innovative entrepreneurship can develop environmentally friendly products and services, reducing negative impacts on ecosystems. Second, small and medium enterprises (SMEs) initiated by local entrepreneurs can provide job opportunities, increase people's income, and empower the community. Third, social entrepreneurship that aims to solve social problems, such as poverty and education, can contribute to the welfare of society. In addition, this article also highlights the challenges faced by entrepreneurs in creating sustainable businesses, including access to capital, technology, and training. Therefore, support from the government and financial institutions is essential to create an ecosystem that supports entrepreneurship. The study concludes that sustainability-focused entrepreneurship not only provides economic benefits, but also strengthens social and environmental structures, thereby contributing to inclusive and sustainable economic development.